Data on Species Composition of Termites (Insecta: Isoptera) in Bac Huong Hoa Nature Reserve, Quang Tri Province - Duc, Nguyen Minh; Lo, Bui Thi; Anh, Do Thi Ngoc; My, Nguyen Thi; Quang, Nguyen Van; Hanh, Trinh Van (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract: For the first time, species composition of termites in Bac Huong Hoa nature reserve has been recorded. We have identified 38 species belonging to 14 genera, 7 subfamilies and two families from this area. Among 14 genera recorded, the genus Odontotermes had the highest number of species and collected sample rate (9 species, accounted for 23.68% of total species number of the studied area collected samples), followed by Schedorhinotermes with six species (15.79%), Reticulitermes and Nasutitermes , with four species each (10.53%). The remaining genera had from one to three species (2.63-7.89%). In comparison with two nearby areas (Dakrong and Bach Ma), species composition of termites in Bac Huong Hoa Nature Reserve was lower than the areas. The result on distribution in different altitudinal bands showed that species number of termites in the altitudinal band 700-1000 m was the highest (26 species, accounting for 68.42%), followed by that in the altitudinal band >1000 m (16 species, 42.10%) and that in the altitudinal band <700 m (10 species, 26.32%). Keywords: Termites, species composition, altitudinal distribution.